Left Ventricular Apical Aneurysm in a Patient with Hypertrophic Cardiomyopathy Diagnostic and Management Dilemmas - Theodoridou, Parthena; Masmanidou, Despoina; Kousidis, Panagiotis; Roumelis, Panagiotis; Tsarouchas, Anastasios; Mouselimis, Dimitrios; Papadopoulos, Christodoulos E (Cardiology and Cardiovascular Medicine, 2019)
We discuss a relatively rare case of a patient with an unclear diagnosis between hypertrophic cardiomyopathy (HCM) accompanied by left ventricular (LV) apical aneurysm and Myocardial Infraction with Non-Obstructive Coronary Arteries (MINOCA) associated with an LV apical aneurysm. A 77-year-old white Caucasian woman presented to a district hospital with angina-like symptoms and elevated high-sensitivity (HS) troponin I. Three weeks later, the patient was re-evaluated with heart failure (New York Heart Association -NYHA- class III) symptoms, particularly fatigue and dyspnoea in less than ordinary activity. To establish the diagnosis an echocardiogram was recommended and it revealed an LV apical aneurysm and concentric LV hypertrophy with a moderately reduced left ventricular ejection fraction (LVEF). Coronary angiography revealed absence of significant obstructive coronary artery disease. To further clarify LV hypertrophy, Cardiac Magnetic Resonance Imaging (CMR) was performed and documented LV apical aneurysm with apical transmural post-infarction fibrosis together with specific patchy myocardial fibrosis of the basal interventricular septum, indicative of hypertrophic cardiomyopathy. The diagnosis of MINOCA in a patient with hypertrophic cardiomyopathy was then established and conservative treatment with dual antiplatelet therapy (aspirin, clopidogrel), ramipril, carvedilol, eplerenone and atorvastatin was offered.